Surgical management of choledocholithiasis: a single institutional experience - Annareddy, Dinakar Reddy; Thota, Anuroop (International Surgery Journal, 2022)
Background: Choledocholithiasis is the 2nd most common complication of gallbladder stone disease and its incidence increases with age. There are different modalities of treatment ranging from endoscopic techniques to open and minimally invasive surgery. However, the single best modality has remained a point of major speculation. This study was undertaken to evaluate various modalities of surgical treatments undertaken at our institute. Methods: A retrospective analysis of all the patients who underwent surgery for common bile duct stones during the study period was done. The parameters analyzed were epidemiological data, clinical parameters, surgical details and any complications. Results: A total of 50 patients were included in the study with a M:F ratio of 1:1. The most common presenting complaint was pain abdomen and the majority, were post ERCP failure cases. The common cause for failure was multiple or impacted stones. Majority of the patients underwent an open surgery and a drainage procedure in the form of choledochoduodenostomy was added. Laparoscopic exploration showed advantage in form of shorter hospital stay, early return to activity. There were no instances of retained or missed stones and the complications were limited to wound complications. Conclusions: In the era of advanced endoscopy, surgery still holds an eminent place in the management of choledocholithiasis. With growing expertise, the complication and clearance rates are better than endoscopy. Laparoscopic exploration can be the single best treatment for patients with both cholelithiasis and choledocholithiasis.